Prevalence of Elective and Ruptured Abdominal Aortic Aneurysm Repairs by Age and Sex From 2003 to 2016 in Ontario, Canada - Salata, Konrad (JAMA Netw Open, 2018)
IMPORTANCE: Age and sex are important considerations in assessing and individualizing therapy for abdominal aortic aneurysm (AAA) repair. OBJECTIVE: To determine the prevalence of open and endovascular elective AAA (EAAA) and ruptured AAA (RAAA) repair by age and sex. DESIGN, SETTING, AND PARTICIPANTS: In this retrospective, population-based, cross-sectional, time-series analysis in Ontario, Canada, from April 1, 2003, to March 31, 2016, all patients undergoing AAA repair who were older than 39 years were included. EXPOSURES: Elective AAA and RAAA repair with open surgical repair (OSR) or endovascular aortic repair (EVAR). MAIN OUTCOMES AND MEASURES: Age- and sex-standardized rates of EAAA and RAAA repair with OSR and EVAR. RESULTS: From 2003 to 2016, 19 489 EAAA repairs (12 232 [63%] OSR and 7257 [37%] EVAR) and 2732 RAAA repairs (2466 [90%] OSR and 266 [10%] EVAR) were identified. The mean (SD) age was 72.7 (8.1) years in the EAAA subgroup and 73.5 (8.9) years in the RAAA subgroup; 15 813 patients (81%) in the EAAA subgroup and 2178 (80%) in the RAAA subgroup were men. The rates of EAAA by age quintile and sex decreased over the study period except among patients older than 79 years (1.3 per 100 000 population in 2003 to 2.2 per 100 000 population in 2016; 70% increase; P < .001). The rates of elective OSR decreased across all age and sex subgroups (range, 38%-74% decrease; P ≤ .009 for all subgroups) except among patients older than 79 years (1.3 per 100 000 population at baseline to 0.56 per 100 000 population in the second quarter of 2016; 53% decrease; P = .05). The rates of elective EVAR significantly increased across all age and sex subgroups (range, 566%-1585% increase; P ≤ .04 for all subgroups). Elective EVAR became the dominant treatment approach for aneurysms in men around 2010, whereas it maintained parity among women in 2016. The RAAA repair rate decreased over the study period in all subgroups (range, 32%-91% decrease; P ≤ .001 for all subgroups), but the decrease was not significant among women (80% decrease; P = .08). Similarly, the rates of ruptured OSR decreased among all subgroups (range, 47%-91% decrease; P < .001), but the decrease was not significant among women (87% decrease; P = .54). Ruptured EVAR showed significant uptake in all subgroups. CONCLUSIONS AND RELEVANCE: Among patients with AAA in Ontario, Canada, use of EVAR appeared to increase from 2003 to 2016, whereas OSR use appeared to decrease. These findings were most pronounced among elective procedures for men and older patients. The delayed increase in the use of EVAR among women may reflect continued anatomical constraints for women seeking elective repair.